Distribution and number of Cajal‐like cells in testis tissue with azoospermia. Issue 4 (28th February 2017) - Hasirci, Eray; Turunc, Tahsin; Bal, Nebil; Goren, Mehmet Resit; Celik, Huseyin; Kervancioglu, Enis; Dirim, Ayhan; Tekindal, Mustafa Agah; Ozkardes, Hakan
Abstract: We investigated the number and distribution of Cajal‐like cells in patients with azoospermia. A total of 99 patients with non‐obstructive azoospermia were divided into subgroups [19 patientsin hypospermatogenesis group (S1), 40 patients in maturation arrest group (S2), 20 patients in a Sertoli cell‐only syndrome (S3), and 20 patients in a testicular atrophy and fibrosis group (S4)], and 20 patients with obstructive azoospermia group (S0). Sections stained with a c‐kit antibody were studied by light microscopy to determine the number and distribution of Cajal‐like cells in peritubular and perivascular areas of testis. The number of Cajal‐like cells were higher in all the non‐obstructive groups than in the obstructive group (S0: 2.43 cells/mm 2, S1: 3.14 cells/mm 2, S2: 4.00 cells/mm 2, S3: 4.57 cells/mm 2, S4: 3.86 cells/mm 2 ) but statistically significantly different ( p < 0.05) in the S2 and S3 subgroups only. Distribution of Cajal‐like cells were similar in all groups. The number and distribution of Cajal‐like cells in non‐obstructive groups suggest that these cells may affect spermatogenesis. This cellular type can be responsible for the regulation of cellular motility or spermatogenesis. Electrophysiological and electron microscopic studies are needed to better define morphology and function of Cajal‐like cells in the testis, especially totally the normal testis tissue.